View of Adolescent Girls about Fashion - Ali, Nazia; Hussain, Ghazal (Nurture, 2008)
Fashion is known to exert an important influence on adolescent girls clothing. However extent of adoption depends on perceptions about fashion and relative importance of perceived benefits of adopting fashion in relation to other personal values. This study was conducted to explore fashion related views of adolescent girls. Data was collected with the help of a questionnaire from a convenient sample of 100 female students of a college. Culturally acceptable styles were perceived more often as fashion than the less acceptable ones. A majority (66%) mentioned refraining form adoption of fashion if challenges the cultural values. It could be concluded that cultural values have a major influence on girls’ perceptions and adoption of fashion.